The Evolutionary Consequences of Dams and Other Barriers for Riverine Fishes. (16th March 2022) - Zarri, Liam J; Palkovacs, Eric P; Post, David M; Therkildsen, Nina O; Flecker, Alexander S
Abstract: Dams and other anthropogenic barriers have caused global ecological and hydrological upheaval in the blink of the geological eye. In the present article, we synthesize 307 studies in a systematic review of contemporary evolution following reduced connectivity and habitat alteration on freshwater fishes. Genetic diversity loss was more commonly observed for small populations impounded in small habitat patches for many generations behind low-passability barriers. Studies show that impoundments can cause rapid adaptive evolution in migration timing, behavior, life history, temperature tolerance, and morphology, as well as reduce phenotypic variance, which can alter adaptive potential and ecological roles. Fish passage structures can restore migratory populations but also create artificial selection pressures on body size and migration. The accelerating pace of dam removals and the paucity of data for fishes other than salmonids, other vertebrates, invertebrates, and tropical and southern hemisphere organisms highlights the urgent need for more studies on the rapid evolutionary effects of dams.